Odpowiedź :
Odpowiedź:
a) 2 - (-2) = -2 + 2
2+2 ≠0
Liczba - 2 nie jest rozwiązaniem tego równania.
b) 3*(-2)= -2 +4
-6 ≠2
Liczba - 2 nie jest rozwiązaniem tego równania.
c) 4*(-2) - (-2)²= 5*(-2) -2
-8 - 4 = -10-2
-12 = - 12
Liczba -2 jest rozwiązaniem tego równania.
d) ( -2 )²-1 = -5
4-1 ≠ -5
Liczba -2 nie jest rozwiązaniem tego równania
Szczegółowe wyjaśnienie:
Odpowiedź:
c.
Szczegółowe wyjaśnienie:
a. 2-(-2)+=-2+2
4=0 - -2 nie jest rozwiązaniem
b. 3*(-2)=-2+4
-6=2 - -2 nie jest rozwiązaniem
c. 4*(-2)-(-2)²=5*(-2)-2
-8-4=-10-2
-12=-12 - -2 jest rozwiązaniem
d. (-2)²-1=-5
4-1=-5 - -2 nie jest rozwiązaniem
3=-5